Kinetic Study of Esterification Reaction - Ahmed Zeki, Nada S.; Al-Hassani, Maha H.; Al-Jendeel, Haider A. (Al-Khwarizmi Engineering Journal, 2010)
The Esterification kinetics of acetic acid with ethanol in the presence of sulfuric acid as a homogenous catalyst was studied with isothermal batch experiments at 50-60°C and at a different molar ratio of ethanol to acetic acid [EtOH/Ac]. Investigation of kinetics of the reaction indicated that the low of [EtOH/Ac] molar ratio is favored for esterification reaction, this is due to the reaction is catalyzed by acid. The maximum conversion, approximately 80% was obtained at 60°C for molar ratio of 10 EtOH/Ac. It was found that increasing temperature of the reaction, increases the rate constant and conversion at a certain mole ratio, that is due to the esterification is exothermic. Activity coefficients were calculated using UNIFAC program. Results showed deviation in activation energy in the non-ideal system of about 20% this is due to the polarities of water and ethanol compared to the non-polar ethyl acetate this dissimilarity leading to strong non- ideal behavior. The homogenous reaction has been described with simple power-law model. The chemical equilibrium combustion calculated form the kinetic model in agreement with the measured chemical equilibrium.